Faktor-Faktor yang Memengaruhi Kinerja dan Kepuasan Tenan di Inkubator Bisnis IPB - Kristianingsih, -; Sumarwan, Ujang; Hasbullah, Rokhani (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
Business incubator is an assistance agency for beginner business which is believed to be able to generate professional, independent, and competitive entrepreneurs. This research aims to identify factors influencing the performance of business incubator’s tenants, and evaluate tenants’s satisfaction during their participation in business incubator. This research is conducted in Business Incubator of IPB by interviewing both inwall tenants and outwall tenants. The data obtained are analyzed using, Wilcoxon test with SPSS software, Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Result of this research reveals that performance of inwall and outwall  tenants are shown by the increase of gross profit, profit, number of employee, increase of product variants, number of customer, participation in training, the presence of business assistance, participation in training, the presence of business assistance, expansion of business place, expansion of business place. marketing expansion or number of agent, and the decline of complaints experienced by tenants. According to the calculation result of IPA,CSI, tenant satisfaction level on business incubator is categorized as good. Factor that is considered need to be improved by Business Incubator of IPB is adequate human resources performance improvement, especially for assistance and service toward tenants.